AN ANALYSIS OF ENERGY INTENSITY AND CAPACITY UTILISATION OF TWO MAJOR ENERGY INTENSIVE MANUFACTURING INDUSTRIES IN INDIA: 1980-81 TO 2011-12 - Bera, Pinki; Mihir Kumar Pal, (IJRDO - Journal of Business Management, 2020)
In this paper, we tried to estimate the Energy Intensity (EI) and Capacity Utilisation (CU) of two major energy intensive industries, Chemical and Chemical Products Industry and Basic Metal industry over the period 1980-81 to 2011-12 and also a comparative analysis for pre and post -liberalisation period. We find that the rate of capacity utilization is less than unity for all observation in Chemical and Chemical Product Industry as well as Basic Metal industry. The energy intensity is increasing in the post-reform period than the pre-reform period.